Model Kegiatan Ekstrakurikuler Kerohanian Islam Keputrian di SMA Negeri 5 Cimahi - Aliyah Putri Fahira; Nan Rahminawati; Dewi Mulyani (Bandung Conference Series: Islamic Education, 2024)
Abstract. This research aims to analyze the model of female activities in the extracurricular activities of Islamic Spirituality at Senior High School 5 Cimahi. The approach, strategies, methods, and impacts of these activities are the main focus of the research. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The activity management method uses a qualitative method with a descriptive approach to gain a deep understanding of the implementation of the activity. The model of female activities held by Islamic Spirituality at Senior High School 5 Cimahi is based on a profound understanding of Islamic teachings regarding women. Through this extracurricular activity, female students are provided a platform to acquire knowledge, skills, and a deeper understanding of Islamic and feminine values. The impact of this female activity includes an improved understanding of Islamic teachings, the formation of better character and morals among the students, as well as the development of practical skills applicable in daily life. This research contributes to understanding the implementation of female activities in the school environment as an effort to shape female students into more skilled and empowered individuals, in accordance with Islamic principles. Abstrak. Penelitian ini bertujuan untuk menganalisis model kegiatan keputrian dalam ekstrakurikuler Kerohanian Islam di SMA Negeri 5 Cimahi. Pendekatan, strategi, metode, dan dampak dari kegiatan tersebut menjadi fokus utama penelitian. Metode penelitian yang digunakan adalah kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Metode pengelolaan kegiatan menggunakan metode kualitatif dengan pendekatan deskriptif untuk mendapatkan pemahaman yang mendalam tentang pelaksanaan kegiatan. Model kegiatan keputrian yang diadakan oleh Kerohanian Islam di SMA Negeri 5 Cimahi didasarkan pada pemahaman mendalam akan ajaran Islam tentang wanita. Melalui kegiatan ekstrakurikuler ini, siswi diberikan wadah untuk memperoleh pengetahuan, keterampilan, dan pemahaman lebih lanjut tentang nilai-nilai keislaman dan kewanitaan. Dampak dari kegiatan keputrian ini mencakup peningkatan pemahaman siswi tentang ajaran Islam, pembentukan karakter dan moral yang lebih baik, serta pengembangan keterampilan praktis yang dapat diterapkan dalam kehidupan sehari-hari. Penelitian ini memberikan kontribusi dalam memahami implementasi kegiatan keputrian di lingkungan sekolah sebagai upaya untuk membentuk siswi menjadi individu yang lebih terampil dan berdaya, sesuai dengan prinsip-prinsip Islam.